KINERJA SAHAM DURABLE GOODS DAN NONDURABLE GOODS MASA KRISIS FINANSIAL GLOBAL - Mohamad Samsul (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2011)
The purpose of this research is to analyze the stock performance of “the durable goods” and “the nondurable goods” during global financial crisis of 2008. The amount of sample used is about 298 kinds of stocks with the data of individual stock index and coupon rate of government bond. The stock performance used Sharpe’s Model. The period of financial crisis divided into two periods: contraction period and recovery period. Hypothesis: (1) there are differences of stock performance between the durable goods and the nondurable goods during each of contraction period and recovery period; (2) there are differences of stock performance between recovery period and contraction period for each of durable goods and nondurable goods. The result of this research showed that: (1) the stock performance of durable goods is insignificantly different than nondurable goods neither for contraction nor recovery period; (2) the stock performance is significantly difference between contraction and recovery period for each of durable goods and nondurable goods. These result was consistant to prior research. Suggestion: the treatment policy of nondurable goods should be the same as durable goods during the contraction and recovery periods, when the global financial market shock occurred